The common-base differential amplifier and applications revisited. (May 2017) - Maundy, B.J.; Ozoguz, Serdar; Elwakil, A.S.; Gift, S.J.G.
Abstract: In this paper, the common-base (or -gate) differential amplifier is revisited and presented. A variant of the same amplifier is also presented and both are analyzed using standard two-port network analysis. Their high frequency behavior, differences in biasing details and noise analysis are also compared and contrasted. New differential input-output filters are derived for the common-base (or -gate) differential amplifier as well as a new low impedance Norton amplifier. Simulations using Spectre in a 90 nm UMC CMOS process of several of the filters as well as experiments conducted using discrete transistors confirm the theoretical results.